Acute Encephalitis with Refractory, Repetitive Partial Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Clinical characteristics and outcome of 29 children (19 male; 10 female) with acute encephalitis with refractory, repetitive partial seizures (AERRPS) were analyzed in a retrospective, multicenter nationwide questionnaire-based study in Japan.